An Equivalent Characterization of $CMO(\mathbb{R}^n)$ with $A_p$ Weights (Journal of Mathematical Study, 2020)
Let $1
Keywords: $BMO_{ω}(\mathbb{R}^n)$; $CMO(\mathbb{R}^n)$; $A_p$; John-Nirenberg inequality.